In vivo and in vitro comparative Study of primary metabolites of Boerhaavia diffusa (L) - Joshi, Dr. Anita (International Journal of Pharmaceutical & Biological Archive, 2017)
Boerhaavia diffusa belonging to family Nyctaginaceae. It is an important medicinal herb. It contains Primary metabolites and secondary metabolites viz., carbohydrates, lipids, alkaloids, flavonoids, essential oils, sterols, lignin and tannins .In this investigations various primary metabolites were observed from Leaf, Stem, and Callus of Boerhaavia diffusa. Protein contents were maximum in Callus and minimum in stem. Carbohydrates contents were maximum in leaf and minimum in Stem. Lipid was observed maximum in leaf and minimum in callus sample.